Enhancement of Colouration in the Goldfish, Carassius Auratus By Dietary Incorporation of Pigment Sources of Plant Origin - Ravikumar Sharma (School of Aquaculture And Biotechnology, 2017)
Abstract- The present study was taken up to assess the potential of using three carotenoid sources of plant origin, for colour enhancement in the gold fish (Carassius auratus). The ingredients tested were two locally available flowers and the peel of one fruit, viz; Allamanda cathartica (golden trumpet), Cassia fistula (golden shower flower) and banana peels, were incorporated in diets for the goldfish @ 5% and the dietary colour enhancement potential of these diets was assessed over a period of 60 days. Fry of gold fish (Carassius auratus), one of the most colourful, attractive and popular aquarium fish were used for the study. The experimental setup consisted of 12 FRP tanks, with 80 litre water capacity. In each tanks 10 nos of gold fish fry were stocked. The experiment was designed in a completely randomized design, with three replications for each treatment. The dried powder of banana peels and dried powder of the flowers, were incorporated in the test diets. The test diets were designated as T1 (with 5% Allamanda powder), T2 (with 5% banana peel powder and T3 (with 5% Cassia powder). A basal feed without addition of carotenoid served as the control (T0). Each diet was fed to fish in a set of three tanks each. Growth response of fishes and water quality were monitored at fortnightly intervals. The colour enhancement in gold fish was observed to be the highest in the treatment T3 followed by T2 and T1. The estimation of carotenoid content in fish was done by spectrophotometric analysis. From the spectrophotometric analysis the maximum carotenoid content of 7.052µg/ g wet weight was observed in fish fed the 5% Cassia fistula incorporated diet, followed by 5% Allamanda cathartica incorporated diets with 6.39µg/ g wet weight, 5% Banana peels with 5.518µg/g wet weight. The lowest carotenoid content of 3.592µg/ g wet weight was in the control fish. The growth response was also highest in the T3 treatment. The plant sources of carotenoids used in the present experiment viz; Allamanda cathartica, Banana peels and Cassia fistula, have the potential to be used as carotenoid sources for enhancement of colour in the gold fish.